Cyanostilbene-based vapo-fluorochromic supramolecular assemblies for reversible 3D code encryption. Issue 7 (21st May 2020) - Gao, Zhao; Chen, Ze; Han, Yifei; Wang, Feng
Abstract : Vapo-fluorochromic 3D code encryption systems have been constructed on the basis of cyanostilbene-based supramolecular assemblies, which open up a new avenue toward smart information protection materials. Abstract : Scanning codes with the capability for stimuli-triggered decryption are urgently needed to prevent information leakage and counterfeiting. Compared to conventional 1D barcodes and 2D QR codes, 3D codes show promise in this field thanks to the presence of four different colors in the icon, with great information variability. Up to now, encrypted 3D code development has primarily focused on chemical reaction-based systems, leading to information decryption in an irreversible transformation manner. Herein, a novel and intelligent 3D code encryption system has been constructed with full reversibility and a fast response, taking advantage of the luminescent vapochromism of cyanostilbene-based supramolecular assemblies. Information in the inkjet-printed 3D code is specifically decrypted through vapor fuming with chlorinated solvents, while it is reversibly encrypted upon removing the vapor. Hence, this study provides a novel and effective strategy for obtaining high-performance smart scanning codes.